Մովսես Խորենացու «Պատմության» լեզվի հունաբան շերտը - Գ. Ս. Մուրադյան (ՀՀ ԳԱԱ հրատ.)
Омонимичность используемых в арменистике терминов հունաբանություն в смысле «грецизм» и «насыщенный грецизмами язык, грецизирующий стиль», приводит иногда к путанице в оперировании самими понятиями. The homonymity of the two terms used in Armeaistics—հունաբանություն in the sense of „hellenizm“ and „hellenizing style“- results sometimes in confusion when operating with the notions themselves.
Keywords: History; Philology; Linguistics; Language and Literature; Medieval History; D History